Periodontal Surgery in Patients With Periodontitis Stage I Grade A - Steffi Triany Arnov; Viona Sekar Melati; Awa Mumtaza Faradiza (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Periodontitis is an inflammation of the periodontal tissue characterized by loss of attachment and gingival enlargement. Periodontal diseases such as periodontitis that cannot be treated with non-surgical therapy, surgical therapy is performed, namely curettage which aims to eliminate bacteria and gingivectomy helps visibility and accessibility so that it will reduce periodontal inflammation. Case: A 21-year-old female patient came to RSGM UNIMUS with complaints of enlarged gingiva on the upper and lower front teeth and redness on the upper left back teeth, since 1 year ago, clinically there was gingival enlargement on teeth 12,21,31,32,42,43 and redness accompanied by periodontal pockets on the mesial and distal parts of teeth 26,27. Case Treatment: The treatment procedure carried out in the initial phase was scaling, then after control it was continued with periodontal surgery, namely curettage and gingivectomy because the results of the evaluation of pocket depth and gingival enlargement did not decrease. Discussions: The results of treatment after two weeks after scaling have not changed, after two weeks after periodontal surgery showed good condition with mild complaints. Conclusion and Suggestions: Gingivectomy and curettage treatment can quickly reduce periodontal inflammation.